The role of biochar in enhancing soil health & interactions with rhizosphere properties and enzyme activities in organic fertilizer substitution - Ali, Aamir; Jabeen, Nida; Chachar, Zaid; Chachar, Sadaruddin; Ahmed, Shoaib; Ahmed, Nazir; Laghari, Azhar Ali; Sahito, Zulfiqar Ali; Farruhbek, Rasulov; Yang, Zhenping (Frontiers in Plant Science, 2025)
Modern agriculture faces a dual challenge: sustainable crop production and reducing the environmental impacts of excessive chemical fertilizers use, which leads to soil degradation, nutrient leaching and declining microbial diversity. Addressing these issues, biochar, a carbon-rich by product of pyrolysis, has emerged as a promising soil amendment due to its ability to enhance soil health, support nutrient cycling, and contribute to climate mitigation. However, its interactive effects with rhizosphere dynamics and soil enzymatic process, particularly when used with organic fertilizers, remain insufficiently explored. This review compiles current knowledge on the short-term and long-term impacts of biochar, particularly in combination with organic fertilizers, on rhizosphere properties, enzyme activities, and nutrient dynamics. In the short term, biochar improves soil structure, water retention, and microbial activity, while reducing nutrient leaching and increasing enzymatic functions. Over the long term, it facilitates carbon sequestration, stabilizes soil organic matter (SOM), and ensures nutrient availability, thereby promoting sustainable crop production. The synergistic application of biochar with organic amendments, such as compost and crop residues, further enhances soil fertility and ecosystem services. Despite its numerous benefits, the adoption of biochar on a larger scale is hindered by challenges related to cost-effectiveness, production consistency, and logistical constraints in diverse agricultural systems. Addressing knowledge gaps related to optimal feedstock selection, pyrolysis conditions, and application rates is essential for maximizing biochar’s potential. By integrating biochar into sustainable agricultural practices, farmers can enhance soil productivity, reduce environmental impacts, and contribute to climate change mitigation. A strategic and evidence-based implementation of biochar technologies holds promise for achieving long-term sustainability and food security goals.